Teaching Grammar Using Pictures - Henny Uswatun Hasanah (OKARA: Jurnal Bahasa dan Sastra, 2015)
Teaching is a process of communication. It has to be created through the way ofteaching and exchanging the message or information by every teacher and student. The message can be knowledge, skills, ideas, experiences, and manyothers. Through the process of communication, the people can receive the message or information. To avoid misunderstanding in the process ofcommunication, media are needed in the process of teaching. Using pictures can make exercises and activities more interesting and more interactive. We canconstantly improve our activities by looking at what went well and what fell flat. These 5 unique ways to practice grammar using pictures are a jumping offpoint, and can be expanded in lots of interesting ways.